Consumming iron tablet is not enought; A perspective from Midwife - Lasiyati Yuswo Yani (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Iron is a mineral that is needed by the body that serves to synthesis hemoglobin. Iron requirement during pregnancy as a result of increased maternal blood supply. Proper iron consumption behavior will affect the levels of hemoglobin during pregnancy. From the literature, the study found six behavior of iron consumption in pregnant women. First Add the amount of food intake. Second Diversity of food intake. Third increase in iron absorption. The four serve the food appropriately. The five regularities of Fe tablet consumption. Last Drink the Fe tablet in the right way. Pregnant women should receive proper counseling on how to properly add blood tablets, as the absorption of tablets plus blood is affected by reinforcing and inhibiting factors. Tablets added blood are easily absorbed if the acidic conditions are in the duodenum and jejunum.